2022
DOI: 10.24252/isafir.v2i2.25485
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Transparansi Dan Akuntabilitas Terhadap Pengelolaan Keuangan Desa Dengan Sifat Amanah Sebagai Variabel Moderasi

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh transparansi dan akuntabilitas terhadap pengelolaan keuangan desa dengan sifat amanah sebagai variabel moderasi (Studi pada desa sekecamatan pallangga kabupaten gowa).  Penelitian ini merupakan penelitian kuantitatif dengan pendekatan penelitian asosiatif. Populasi dalam penelitian ini adalah desa sekecamatan Pallangga kabupaten Gowa. Teknik pengambilan sampel dalam penelitian ini adalah purposive sampling, adapun sampel dalam penelitian ini adalah perangkat d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The principals are the regional government or central government and the local community. This result supports the results of Alfiani & Estiningrum (2021), Sugiharti & Hariani (2021), Anggrayeni, Wawo, & Jannah (2021), Garung & Ga (2020), Tahir, Malia, & Faisol (2020), Dewi, Ikbal, & Moh (2019), Putra & Rasmini (2019), Risya & Nurodin (2017) which showed that accountability affected village financial governance.…”
Section: Effect Of Accountability On Village Financial Governancesupporting
confidence: 88%
See 3 more Smart Citations
“…The principals are the regional government or central government and the local community. This result supports the results of Alfiani & Estiningrum (2021), Sugiharti & Hariani (2021), Anggrayeni, Wawo, & Jannah (2021), Garung & Ga (2020), Tahir, Malia, & Faisol (2020), Dewi, Ikbal, & Moh (2019), Putra & Rasmini (2019), Risya & Nurodin (2017) which showed that accountability affected village financial governance.…”
Section: Effect Of Accountability On Village Financial Governancesupporting
confidence: 88%
“…Therefore, strong accountability is expected for the sustainability of governance, and the plans run according to the will of the principal. This is in line with the findings of Alfiani & Estiningrum (2021), Sugiharti & Hariani (2021), Anggrayeni, Wawo, & Jannah (2021), Garung & Ga (2020), Tahir, Malia, & Faisol (2020), Dewi, Ikbal, & Moh (2019), Putra & Rasmini (2019), Risya & Nurodin (2017) which showed that accountability affected village financial governance. However, it is different from the findings of Sari, Arza, & Taqwa (2019) which showed that accountability had no effect on the village's financial governance.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations